TOTAL ACID NUMBER REDUCTION OF NAPHTHENIC ACIDS USING SUBCRITICAL METHANOL WITH AND WITHOUT ACIDIC IONIC LIQUIDS - ZAFAR, FAISAL (2017)
The impurity, naphthenic acids (NAs), present in heavy crude oil create corrosion problem at different processing stages of oil and gas industry. The traditional total acid number (TAN) reduction processes are non-selective due to their respective drawbacks. The objective of this study was to reduce TAN ofNAs using subcritical methanol with and without acidic ionic liquids (AILs). In this work, commercial NAs, methanol and four AILs consisting of hydrogen sulfate anion and imidazolium cation with varying alkyl chain length were used. The experiments were conducted in a batch reactor. TAN was estimated using ASTM D97 4 method and reaction products were analyzed using FT -IR spectroscopy. Initial investigation using non-catalytic subcritical methanol showed that approximately 59% TAN reduction was achieved at a temperature of 21 0°C, a methanol partial pressure of2 MPa and a reaction time of 150 min.